2007
DOI: 10.1111/j.1553-2712.2007.tb01856.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Statistics: Missing Data in Clinical Research—Part 2: Multiple Imputation

Abstract: In part 1 of this series, the authors describe the importance of incomplete data in clinical research, and provide a conceptual framework for handling incomplete data by describing typical mechanisms and patterns of censoring, and detailing a variety of relatively simple methods and their limitations. In part 2, the authors will explore multiple imputation (MI), a more sophisticated and valid method for handling incomplete data in clinical research. This article will provide a detailed conceptual framework for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
184
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(185 citation statements)
references
References 37 publications
0
184
0
1
Order By: Relevance
“…18 -21 In large populations (n Ͼ 1000) and with 20 databases imputed, as in our study, this technique has been shown to handle up to 90% missing values with a validity and precision of the imputed values almost identical to the "true" values. 22,23 To avoid potential artifacts, we measured ACR in three nonfrozen urine samples within 5 d. This is highly recommended 24,25 and could give more accurate results than a single measurement. Other limitations may be attributed to the imprecision of the Modification of Diet in Renal Disease (MDRD) formula in the range of near-normal values leading to risk category misclassification of some participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 -21 In large populations (n Ͼ 1000) and with 20 databases imputed, as in our study, this technique has been shown to handle up to 90% missing values with a validity and precision of the imputed values almost identical to the "true" values. 22,23 To avoid potential artifacts, we measured ACR in three nonfrozen urine samples within 5 d. This is highly recommended 24,25 and could give more accurate results than a single measurement. Other limitations may be attributed to the imprecision of the Modification of Diet in Renal Disease (MDRD) formula in the range of near-normal values leading to risk category misclassification of some participants.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Stata command "ice," we created 20 complete data sets to achieve maximum accuracy. 22,23 Subsequently, the Stata command "micombine" was used together with standard statistical methods, giving unbiased risk estimates with correct CIs. For most individuals without diabetes and hypertension, data were missing completely at random, and for those who did not return urine samples as requested, data were assumed to be missing at random, thus meeting the assumptions of the method.…”
Section: Concise Methodsmentioning
confidence: 99%
“…7 This mechanism requires the pattern of censored values to be completely ''explained,'' or dependent on, observed values in the sample but not dependent on any unobserved or missing values. 8,11,12 In other words, in a given data set (Y) consisting of observed values (Y obs ) and missing values (Y mis ), MAR is present if the probability that a value is censored is dependent only on Y obs and not on Y mis .…”
Section: Marmentioning
confidence: 99%
“…8,10 As this relates to the discussion of MI in the second article of this series, the between-imputation variance is assumed to be zero because only one value exists. 7 Stochastic Regression Imputation. Stochastic regression imputation provides an additional level of sophistication to regression imputation by replacing censored values with the predicted value from a regression analysis plus its residual error.…”
Section: Weighted Complete-case Analysismentioning
confidence: 99%
See 1 more Smart Citation